Characterization of the autumn microphytobenthos and phytoepiphyton of the littoral of Lake Verbne (Kyiv, Ukraine) - Hrygor’yeva, G.Ye. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2025)
For the first time, the taxonomic diversity, quantitative development, structural organization, dominant complexes, trophic status of microphytobenthos and phytoepiphytos were determined for the littoral of the Lake Verbne ecosystem in the autumn period (2023). The taxonomic richness of the microphytobenthos and phytoepiphyton was formed by 117 species (135 intraspecific taxa, ist) from 7 divisions, and 79 species (87 ist) from 6 divisions. Among the divisions, the leading role in the floristic spectrum belonged to Bacillariophyta (52; 64%), followed by Chlorophyta (27; 20%) and Cyanobacteria (6; 8%), respectively. The Sørensen coefficient between microphytobenthos and phytoepiphyton was 0.48, at the level of divisions: Bacillariophyta > 0.57 > Cyanobacteria > 0.53 > Chlorophyta > 0.42, which confirms a certain specificity of the taxonomic composition of the components of the studied contour communities. The quantitative diversity of these algal communities was formed by the oligodominant complexes Cyanobacteria—Bacillariophyta (by number) and Bacillariophyta—Cyanobacteria (by biomass). The trophic status of the lake ecosystem littoral according to microphytobenthos corresponds to the eutrophic type, and according to phytoepiphyton — to the oligotrophic type. Shannon's indices of information diversity, calculated taking into account the biomass (the energy basis of primary energy flows), were higher for microphytobenthos than for phytoepiphyton. The dominant complex of contour algal communities was oligo- or polydominant: Cyanobacteria—Bacillariophyta (by number) and BacillariophytaCyanobacteria (by biomass), represented by both small-celled and large-celled forms. The original data on the structural organization of microphytobenthos and phytoepiphyton indicate an important role of contour algal communities in the autumn in the formation of biodiversity in the littoral of Lake Verbne, which is a hydroecosystem of the metropolis and belongs to the nature reserve fund of Ukraine.